Perancangan Komponen Sistem Hidrolik Pada Mesin Press Kapasitas 50 TON - Apriel Fernandus Nainggolan; Herisiswanto Herisiswanto; Dedi Rosa Putra Cupu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Hydraulic press machine is a device that is used to mass produce a component with the same shape and size, so that it becomes the desired production item. In this research is proposed to design the component of a hydraulic press machine system for a maximum capacity of 50 ton. The design was begins by observing the needs and workings of the system, followed by analysis and calculation components of hydraulic system, then engineering drawings and completion. The results design was obtained a hydraulic system capacity of 50 ton, then determined the working fluid pressure (P) of 250 bar = 250. 105N / m2. Loading force is obtained to calculate things related to the hydraulic system namely cylinder dimensions and load holding strength, the workings of the system to determine the main components and determine the flow rate capacity in the cylinder. From the results of the calculation, the maximum loading force = 490,500 N, the maximum tensile stress = 1172 N / mm2, and the material permit stress = 116.5 N / m2, with the material used is nickel molybdenum chromium steel (JIS G4103 SNCM25). Analysis results show that it is proven to work as expected. Keywords: Hydraulic system, Pressure, Hydraulic cylinder